Ответы и объяснения

2014-02-16T08:19:56+00:00
Система двух уравнений с двумя неизвестными
b₂ = b₁q = -2
b₇ =  b₁q⁶ =  \frac{1}{16}  ⇒ b₁q * q⁵ =  \frac{1}{16}

                                                         -2 * q⁵ =  \frac{1}{16}      

                                                            q⁵ = -  \frac{1}{32}       

                                                              q = -  \frac{1}{2}     

b₄ = b₁q₃ = -2 * ( -  \frac{1}{2}  )² =  -  \frac{1}{2}     

Комментарий удален
Комментарий удален